A decade of Tanzania politics, economy and society 2005-2017 - Hirschler, Kurt; Hofmeier, Rolf 1939- (Brill, 2019)
Tanzania is widely recognized as a rather exceptional case of an African country that has seen political continuity and stability for more than five decades and has not experienced any major conflicts as has been the case elsewhere on the continent. Major political transformations - such as the transformation from a socialist one-party state to a market-oriented multi-party system - were initiated from above and controlled by the Revolutionary Party CCM, which has ruled the country since it gained independence in 1961. Despite its peaceful development and steady economic growth rates over the past 15 years, Tanzania has remained a low-income country with a huge majority of its people living in poverty. This volume contains the original country chapters on Tanzania from the Africa Yearbook. Politics, Economy and Society South of the Sahara, covering the period 2005 - 2017. It embraces the entire 10-year presidency of President Kikwete and the first two years under the current President Magufuli. -- Back cover
Keywords: Geschichte 2005-2017; Wirtschaft; Gesellschaft; Politik; Tansania; Tanzania / Politics and government / 21st century; Tanzania / Economic conditions / 21st century; Tanzania / Social conditions / 21st century